2011
DOI: 10.1037/a0022186
|View full text |Cite
|
Sign up to set email alerts
|

Alliance in individual psychotherapy.

Abstract: This article reports on a research synthesis of the relation between alliance and the outcomes of individual psychotherapy. Included were over 200 research reports based on 190 independent data sources, covering more than 14,000 treatments. Research involving 5 or more adult participants receiving genuine (as opposed to analogue) treatments, where the author(s) referred to one of the independent variables as "alliance," "therapeutic alliance," "helping alliance," or "working alliance" were the inclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

88
1,349
6
83

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,710 publications
(1,560 citation statements)
references
References 29 publications
88
1,349
6
83
Order By: Relevance
“…The PITQ-p also demonstrated statistically stronger relationships with measures of emotional dysregulation and psychological quality of life than the PITQ-t. These findings are consistent with research indicating a stronger relationship between patients’ reports (vs. therapist reports) of alliance and treatment outcome (Horvath et al, 2011), and underscore the salience of querying patients’ perceptions about their progress in treatment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The PITQ-p also demonstrated statistically stronger relationships with measures of emotional dysregulation and psychological quality of life than the PITQ-t. These findings are consistent with research indicating a stronger relationship between patients’ reports (vs. therapist reports) of alliance and treatment outcome (Horvath et al, 2011), and underscore the salience of querying patients’ perceptions about their progress in treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Lambert, 2015) resulted in improved outcomes for patients demonstrating difficulties in making or sustaining treatment gains. A meta-analysis of 201 therapeutic alliance studies comprising over 14,000 treatments (Horvath, Del Re, Flückiger, & Symonds, 2011) found that patient-reported alliance data were generally more strongly predictive of therapeutic outcome than therapist-reported data. These findings prompted the first and second authors to develop a patient version of the PITQ.…”
Section: Development Of the Pitq-p And Pitq-tmentioning
confidence: 99%
“…This relationship has previously been established as an important predictor of outcome in psychotherapy [1,2], and has been viewed as one of the most important 'common factors' that explain the success of professional interventions when the specific factors connected to the design and theory of these interventions does not suffice to explain the outcome [3]. Services of support and treatment that is directed toward persons with SMI take place within a wealth of organizational contexts such as psychiatric inpatient care, community mental health services and support provided in people's homes [4].…”
Section: Introductionmentioning
confidence: 98%
“…Behavioral outcome research also includes a successive hierarchy of contrast conditions assumed to control for non-specific therapy effects [1]. Very often, this process continues until the treatment fails in contrast to another specific treatment [2] or, worse yet, in an effectiveness study where the method is pitted against usual care [3][4][5][6]. In meta-analyses that do not account for variation in control group magnitude, the end result is a small effect size [7].…”
Section: Branding Addiction Therapies and Reified Specific Factorsmentioning
confidence: 99%
“…I agree that the field of behavioral intervention research needs to move beyond a hyper-focus on standardized empirically supported treatments. However, as therapist factors overall account for only 3-7% of the variance in client outcomes [3,4], will studying the therapeutic context be sufficient to boost the effects of addiction treatments? Instead, perhaps the way beyond this long-held debate is to focus upon [1] specific techniques predicting outcomes, [3] stand-alone technologies and [4] broadening the focus to include cost-effectiveness.…”
mentioning
confidence: 99%